Particle film effects on the ecophysiological parameters of two arboreal species under water restriction - Santos, Anderson Dos; de Lima, Roberta Samara Nunes; Lima, Emerson de; Jardim, Alexandre Maniçoba da Rosa Ferraz [UNESP]; Silva, Elania Freire da; Ferreira Júnior, Ricardo Araújo; Moura, Flávia de Barros Prado; Silva, José Vieira (FapUNIFESP (SciELO), 2024)
The objective of this study was to evaluate the effects of using particle film associated with two water regimes on the ecophysiological parameters of young plants of two species native to the Brazilian semiarid region (Tabebuia aurea and Ziziphus joazeiro). The experiments were conducted in randomized blocks in a 2 × 2 factorial design, with nine replications. The treatments used were the application of particle film (Surround® WP) at a concentration of 5% and without film or 0%, and two irrigation water regimes based on reference evapotranspiration (ETo), irrigated with 100% of ETo and not irrigated or 0% of ETo. Gas exchange determinations were performed at 0, 15, 30, and 45 days after treatments imposition, while the analyses of photosynthetic pigments were carried out only at the end of the experiment. The species Tabebuia aurea and Ziziphus joazeiro showed tolerance to water stress, demonstrated by their high water use efficiency. On the other hand, the application of particle film caused an increase in stomatal conductance, transpiration, and intrinsic water use efficiency and reductions in leaf temperature and instantaneous water use efficiency in plants of both species studied. The particle film was efficient in providing photoprotective properties verified by the increase in the content of photosynthetic pigments. However, the use of this film requires more in-depth investigations, which could allow a better understanding of its management in tree species in the Brazilian semiarid region.
Efeitos do filme de partículas nos parâmetros ecofisiológicos de duas espécies arbóreas sob restrição hídrica
Keywords: Caatinga; Gas exchange; Photochemistry; Photosynthetic pigments; Thermal stress